Meaning and Social Function in the Film Catatan Harian Menantu Sinting - Putri Adelina Br Situmorang (TALENTA Publisher, 2026)
This study examines the meaning and social function represented in the Indonesian comedy film Catatan Harian Menantu Sinting by exploring the interaction between Batak local wisdom and contemporary family life. The study aims to identify the central meanings conveyed through the film and to analyze its social functions using Bronislaw Malinowski’s functionalism theory. A qualitative descriptive approach was employed through content analysis of the film’s narrative, characters, dialogues, and cultural representations. The findings reveal that the film portrays the tension between traditional Batak values and modern perspectives on marriage, gender, family, and personal identity. Fourteen major thematic ideas were identified, highlighting issues such as lineage expectations, intergenerational conflict, marital communication, emotional resilience, gender inequality, and cultural adaptation. The film functions not only as entertainment but also as a medium for cultural education, social criticism, and the preservation of local wisdom. Through humor and relatable family conflicts, it encourages audiences to reflect on the importance of balancing respect for tradition with individual autonomy and changing social realities. Furthermore, the film demonstrates that open communication, empathy, and mutual understanding are essential for resolving conflicts within extended families. This study concludes that Catatan Harian Menantu Sinting successfully transforms Batak cultural values into a contemporary cinematic narrative that promotes cultural continuity while encouraging critical reflection on tradition in modern Indonesian society.